Proceedings of the 2018 World Wide Web Conference on World Wide Web - WWW '18 2018
DOI: 10.1145/3178876.3186097
|View full text |Cite
|
Sign up to set email alerts
|

Hiding in the Crowd

Abstract: Browser fingerprinting is a stateless technique, which consists in collecting a wide range of data about a device through browser APIs. Past studies have demonstrated that modern devices present so much diversity that fingerprints can be exploited to identify and track users online. With this work, we want to evaluate if browser fingerprinting is still effective at uniquely identifying a large group of users when analyzing millions of fingerprints over a few months.We analyze 2,067,942 browser fingerprints col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 22 publications
0
35
0
1
Order By: Relevance
“…Finally, another challenge is to understand exactly in which circumstances fingerprinting is effective for tracking. While Panopticlick [77] and AmIUnique [88] showed a high rate of fingerprint uniqueness, the Hiding in the Crowd study [83] highlighted the potential demographic issues in browser fingerprinting research. Depending on the targeted audience and the type of users who connects to a website, the capacity to track users with only their fingerprint can greatly vary.…”
Section: Sciencementioning
confidence: 97%
See 2 more Smart Citations
“…Finally, another challenge is to understand exactly in which circumstances fingerprinting is effective for tracking. While Panopticlick [77] and AmIUnique [88] showed a high rate of fingerprint uniqueness, the Hiding in the Crowd study [83] highlighted the potential demographic issues in browser fingerprinting research. Depending on the targeted audience and the type of users who connects to a website, the capacity to track users with only their fingerprint can greatly vary.…”
Section: Sciencementioning
confidence: 97%
“…Hiding in the Crowd. In 2018, Gómez-Boix et al analyzed 2,067,942 fingerprints collected on one of the top 15 French websites [83]. Their findings provide a new layer of understanding to the domain as 33.6% of fingerprints from their dataset were unique.…”
Section: Large Scale Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They also demonstrated that fingerprinting mobile devices is possible, as 81% of mobile fingerprints were unique. In our recent work [14], we analyzed the effectiveness of browser fingerprinting at identifying a large group of users. We observed that some elements can affect the effectiveness of browser fingerprinting at tracking users as only 33.6% of more than two million fingerprints we analyzed were unique.…”
Section: Browser Fingerprint Diversitymentioning
confidence: 99%
“…They also demonstrated that mobile fingerprinting is possible, as 81% of fingerprints from mobile devices were unique in their dataset. The latest study in browser fingerprint diversity, performed by Gómez-Boix et al [14], analyzed more than 2 million fingerprints. The study raises some new questions on this domain, as only 33.6% of the fingerprints collected were unique.…”
mentioning
confidence: 99%